2019
DOI: 10.1029/2019gl082447
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Interflow to Groundwater Recharge in a Snowmelt‐Dominated Headwater Basin

Abstract: Understanding the sensitivity of groundwater generation to climate in a mountain system is complicated by the tight coupling of snow dynamics to vegetation and topography. To address these feedbacks, we combine light detection and ranging (LiDAR)‐derived snow observations with an integrated hydrologic model to quantify spatially and temporally distributed water fluxes across varying climate conditions in a Colorado River headwater basin. Results indicate that annual groundwater flow is an important and stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 55 publications
8
95
2
Order By: Relevance
“…Our results showed that less snow led to a lower snowmelt contribution to total runoff and to lower spring groundwater recharge with larger differences for catchments with higher S f . These results correspond to other studies (Carroll et al, 2019;Cochand et al, 2019;Meriö et al, 2019). However, it does not necessarily mean that summer baseflow and potentially low flows are lower as well, since both the baseflow and low flows are more influenced by other water balance components, such as precipitation and evapotranspiration during spring and summer (Floriancic et al, 2019;Jenicek et al, 2016).…”
Section: Influence Of Snow Storages On Summer Baseflow and Deficit Vosupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that less snow led to a lower snowmelt contribution to total runoff and to lower spring groundwater recharge with larger differences for catchments with higher S f . These results correspond to other studies (Carroll et al, 2019;Cochand et al, 2019;Meriö et al, 2019). However, it does not necessarily mean that summer baseflow and potentially low flows are lower as well, since both the baseflow and low flows are more influenced by other water balance components, such as precipitation and evapotranspiration during spring and summer (Floriancic et al, 2019;Jenicek et al, 2016).…”
Section: Influence Of Snow Storages On Summer Baseflow and Deficit Vosupporting
confidence: 90%
“…For the groundwater recharge, the topography is important, as the water is transported from steep terrain surrounding mountain ridges to lower elevations (Carroll et al, 2019). Therefore, higher elevations are important for catchment storage (Floriancic et al, 2018;Hood and Hayashi, 2015;Staudinger et al, 2017) as well as for stabilizing the streamflow at lower elevations especially during drought periods (Carroll et al, 2019;Cochand et al, 2019). Higher snowpack disproportionally feeds groundwater leading to more streamflow (Barnhart et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The steep slopes, high relief and convergent topographic features of EBC can result in an uninterrupted supply of certain solutes such as P and SO 4 . Carroll et al (2019) also noted that recharge in the Copper Creek sub-catchment appears to be decoupled from annual climate variability, resulting in a steady supply of certain solutes.…”
Section: Analysis Of C-q Hysteresis Patternsmentioning
confidence: 99%
“…This suggests a mountain aquifer permeability threshold below which absolute MBR rates may be insensitive to warming and associated declines in precipitation available for infiltration. Other studies have found that recharge to mountain aquifers composed of fractured crystalline rock (i.e., lower K) commonly may be permeability limited rather than precipitation limited (Carroll et al, ; Flint et al, ; Manning & Solomon, ). Furthermore, Manning () concluded that the absolute MBR rate from the crystalline‐rock Sangre de Cristo Mountains, New Mexico, USA, probably decreased little from the cooler, wetter Pleistocene to warmer, drier Holocene epochs based on NGTs and radiocarbon ages from wells in the adjacent Española Basin.…”
Section: Mbr Reviewmentioning
confidence: 99%